NUDGING LIFE INSURANCE HOLDINGS IN THE WORKPLACE. (6th September 2016) - Harris, Timothy F.; Yelowitz, Aaron
Abstract : Using data from a university, we analyze a policy designed to increase employer‐sponsored life insurance. The university increased basic life insurance holdings, which nudged employees with supplemental coverage to have more life insurance. In large part due to inertia, the nudge increased life insurance holdings one‐for‐one for those who could have undone it. Additionally, we find that expanding coverage options significantly increased total life insurance holdings for new hires who were not subject to inertia. These policy changes reduced uninsured vulnerabilities for two‐thirds of employees. Our findings have important policy implications for addressing widespread disparities in life insurance coverage. ( JEL D31, G22, D03, J32, J33, J38, H20)